Odontoma complexo no cão - Santos, Murilo Nogueira dos; Costa, Victório de; Aguirre, Raul Fernandes (Revista do Centro de Ciências Rurais, 2008)
É descrito um odontoma complexo na região dos dentes molares do ramo direito da mandíbula de um cão de um ano. Esta é a primeira descrição desse tipo de tumor feita no Brasil.AbstractA complex odontoma occurring in a one-year-old mala dog is related. The tumor was in the site of the molar teeth, right side of the mandible. This is the first description of this tumor in Brazil.